The beginner's photography guide - Gatcum, Chris (London Dorling Kindersley Limited, 2016)
Presents step-by-step digital SLR camera basics, while introducing and demonstrating a wide variety of techniques.
Equipment -- Exposure -- Focusing -- Lenses -- Available light -- Flash -- Image enhancement.
Includes index.
Keywords: Photography